The extent to which the general secondary questions Exam (Tawjihi) for Physics in Jordan have taken into account Bloom’s cognitive levels during the years (2015- 2019) - Al- Shurfat, Mashor Saker Mfadi (Journal of Educational and Psychological Sciences, 2020)
This study aimed to know the extent to which the general secondary questions exam (Tawjihi) for physics in Jordan in light of bloom’s cognitive levels during the years (2015- 2019). Which consisted of (50) major questions, includes (399) sub-questions, where the sub-question was considered a unit of analysis. The researcher adopted the intentional method in selecting the sample and used the descriptive analytical approach to conduct the study, where he used a card to analyze the levels of cognitive levels according to the classification of (Bloom). The stability of the tool was confirmed. The percentages used the arithmetic mean of the statistical treatment, the results showed that the ministry’s questions for the physics research focused on the lowest thinking levels (95%), where the level of application came in the first place (62%), understanding in the second (22%), and remembering in the third (11%). While it showed weakness in the focus on the higher thinking levels, the level of analysis got (5%), and there was no level of synthesis and evaluation, and the percentages of the levels are not constant during the years (2015- 2019). The study recommended that the questions should be distributed fairly, especially at the higher thinking levels, and trains the authors of the questions in preparing and formulating the questions in a manner consistent with cognitive levels of Bloom’s classification.